Cytidine 5'-diphosphate reductase activity in phytohemagglutinin stimulated human lymphocytes. - Tyrsted, G (1979)
The optimal conditions and the effect of deoxyribonucleoside triphosphates were determined for CDP reductase activity in PHA-stimulated lymphocytes. The enzymatic reaction showed an absolute requirement for ATP. In the absence of ATP, only dATP showed a minor stimulation of the reduction of CDP to dCDP. During transformation the CDP reductase activity reached a maximum at the same time as the four deoxyribonucleoside triphosphate pools, corresponding to mid S-phase at about 50 h after PHA addition. The DNA polymerase activity reached a maximum at 57 h.